A PRRS CAP update on the regional control and elimination of PRRSV - Raymond R Rowland R (Kansas Agricultural Experiment Station Research Reports, 2011)
The control and elimination of porcine reproductive and respiratory syndrome virus (PRRSV) represents one of the most challenging tasks facing the swine industry world- wide. Several factors related to the biology of the virus make disease detection and elimination difficult. Efforts are further hampered by a lack of vaccines that can protect naïve herds from infection. With this in mind, elimination efforts that incorporate existing tools and knowledge are being initiated. The principal focus is at the region level. One example of success is the Stevens County project in Minnesota, which has attained a PRRSV-negative status and has been expanded to include all of northern Minnesota.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; PRRSV control and elimination; PRRSV